ESTABLISHING THE POLICY OF ENGLISH LANGUAGE ACROSS THE CURRICULUM: ASPECTS OF TEACHERS’ DISTRUST OF THEORY - Eguare, Sulaiman O. (Sokoto Educational Review, 2020)
The paper examined the theories of Kohn, Novak, Barnes, Allen, Britton,’ and Pring on the learning process. Kuhn’s model of ever-expanding paradigms is seen as not appropriate to the advancement of knowledge in the field of education because of the unverifiable nature of his theory. Novak. Barnes, Allen, Britton and Pring insist that student talk is central to the learning process; that teachers should not be transmitters of knowledge. The paper demonstrated that this is basically wrong as this theory has made teachers to be encouraging uncritical pupil talk. All authority of the teacher is rejected. Pring’s theory further compounded the theoretical map of the teacher by suggesting that our conceptual goggle is as valid as the students. The paper concludes on a positive note that we should not play down theory in language and learning by concentrating on the problem but we should provide teachers with conceptual goggle in order to comprehend theories.